X-ray diffraction study of high temperature reaction products in the barium oxide-silica-alumina-ferric oxide system - Strydom, C.A. (Christiena Adriana) (University of Pretoria, 2013)
Thesis (PhD (Chemistry))--University of Pretoria, 2007.